Analisis Volatilitas Indeks Harga Saham Gabungan : Dampak Indeks Saham ASEAN dan Faktor Makroekonomi Indonesia - Suci Rahmadini; Idris (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to analyze the influence of ASEAN stock indices and macroeconomic factors on the Indonesian Composite Index (IHSG) in Indonesia. With increasing global economic uncertainty, it is important for investors to understand the factors that influence stock market volatility. This study focuses on how the relationship between stock indices in ASEAN countries and macroeconomic variables such as interest rates and exchange rates affect the IHSG. The method used in this study is the GARCH (Generalized Autoregressive Conditional Heteroskedasticity) model to analyze monthly time series data from 2019 to 2023. The data used was obtained from Bank Indonesia and the investing.com website. A stationarity test was conducted to ensure that the data used met the analysis requirements, followed by estimation of the GARCH model to determine the relationship between the independent variables and the IHSG. The results show that the PSE, KLSE and STI indices have a positive and significant effect on the IHSG, while the SET index has a positive but insignificant effect on the IHSG, while the exchange rate shows a significant negative effect. These findings suggest that the volatility of the IHSG is strongly influenced by the movement of ASEAN stock indices and exchange rate fluctuations. Based on the results, it is recommended that the government increase bilateral cooperation with ASEAN countries to encourage investment and increase firm value in the market. Investors are also expected to consider external factors in making investment decisions, especially in the midst of global economic uncertainty. In addition, better risk management strategies are needed to deal with high market volatility.